2014
DOI: 10.1002/mrd.22343
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐derived growth factor BB and DD and angiopoietin1 are altered in follicular fluid from polycystic ovary syndrome patients

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrinological pathology among women of reproductive age, and is characterized by abnormalities in ovarian angiogenesis, among other features. Consistent with this association, follicular fluid (FF) concentration and ovarian expression of vascular endothelial growth factor (VEGF) are increased in PCOS patients. In this study, we examined the protein levels of platelet-derived growth factor (PDGF) BB and DD (PDGFBB and PDGFDD), angiopoietin 1 and 2 (ANGPT1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 61 publications
(75 reference statements)
0
29
0
Order By: Relevance
“…VEGF is the main initiator of angiogenesis, and acts by stimulating endothelial cell proliferation. Establishing a mature vascular network, however, requires the coordinated action of many additional factors, including Angiopoietins 1 and 2, which act via the tyrosine kinase receptor, Tie‐2 (Maisonpierre et al, ), and Platelet‐derived growth factor B (Carmeliet & Jain, ; Scotti et al, ). Together, these pro‐angiogenic factors recruit peri‐vascular cells that mature and stabilize newly formed capillaries (Maisonpierre et al, ; Suri et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is the main initiator of angiogenesis, and acts by stimulating endothelial cell proliferation. Establishing a mature vascular network, however, requires the coordinated action of many additional factors, including Angiopoietins 1 and 2, which act via the tyrosine kinase receptor, Tie‐2 (Maisonpierre et al, ), and Platelet‐derived growth factor B (Carmeliet & Jain, ; Scotti et al, ). Together, these pro‐angiogenic factors recruit peri‐vascular cells that mature and stabilize newly formed capillaries (Maisonpierre et al, ; Suri et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The alterations first described in women with PCOS were the increased VEGF concentration and ovarian blood flow (Aleem and Predanic, 1996;Battaglia et al, 1995;Kamat et al, 1995;Zaidi et al, 1995). Besides other angiogenic-related alterations in women with PCOS ovaries (Scotti et al, 2014;Tal et al, 2013aTal et al, , 2013bTal et al, , 2014Xu et al, 2011); (Artini et al, 2006;Hammadeh et al, 2003), we have previously shown that the concentration of ovarian PDGFB and PDGFD is decreased in the DHEA-induced PCOS rat model and in follicular fluid from PCOS patients (Scotti et al, 2014).…”
Section: Discussionmentioning
confidence: 79%
“…In particular, we and others have previously demonstrated that women with PCOS have higher follicular fluid concentrations of VEGF and ANGPT1 (Kamat et al, 1995;Scotti et al, 2014;Stanek et al, 2007) and an increase in ovarian stromal blood flow (Aleem and Predanic, 1996;Battaglia et al, 1995;Zaidi et al, 1995). We have recently described that PDGFB and PDGFD concentration in follicular fluid from PCOS patients are decreased compared to those of control patients (Scotti et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The PDGF family members include PDGF-A, PDGF-B, PDGF-C, and PDGF-D. Kalu et al detected level of factors including IL-6, TNF-ɑ and PDGF in serum from infertile women and women without endometritis [31]. Scotti et al found that PDGF-BB and PDGF-DD were significantly decreased in the follicular fluid of PCOS patients [32]. However, no report has examined the changes of PDGF-D in serum of PCOS patients.…”
Section: Discussionmentioning
confidence: 99%